The bibliographic impact of epidemiological studies: what can be learnt from citations?. Issue 3 (9th October 2009) - Leclerc, Annette; Chastang, Jean-François; Kaniewski, Nadine; Cyr, Diane; Ozguler, Anna; Descatha, Alexis
Abstract : Objective: To document one dimension of the impact of an epidemiological study through citations in scientific journals. Methods: Two sets of articles from studies performed in France were considered. They presented original results on occupational risk factors for low back pain and upper limb disorders. Citations of these articles were retrieved through the Web of Science and Google Scholar, and selected according to several criteria. Most citations present in the Web of Science were also retrieved from Google Scholar, except for the most recent articles. In the Web of Science, after exclusion of self-citations and duplicates, the total number of citations was 109 from 23 different countries for the low back pain articles, with 96 citations from 18 countries for upper limb disorders. A relatively large number of the citations belonged to clinical journals outside the fields of occupational health, ergonomics and public health. Conclusion: This study suggests that results dealing with occupational health disseminate into various fields of clinical research. However, this is only one dimension of the impact of a study.